2009
DOI: 10.3354/ame01347
|View full text |Cite
|
Sign up to set email alerts
|

Probing the bioavailability of organically bound iron: a case study in the Synechococcus-rich waters of the Gulf of Aqaba

Abstract: The bioavailability of organically chelated and ambient iron to phytoplankton in the Gulf of Aqaba was examined in 2 sets of grow-out incubations amended with major nutrients and increasing concentrations of the model organic ligand desferrioxamine B (DFB). Short-term uptake of pre-complexed 55 FeDFB was then conducted with the DFB-incubated natural populations. Since incubation communities were dominated by Synechococcus spp., short-term FeDFB uptake experiments with Synechococcus WH8102 cultures complemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…The surprising similarity of S.A. normalized Fe 0 uptake between cyanobacteria and eukaryotic phytoplankton ( Figure 5) implies that similar factors may be responsible for the upper limit on Fe uptake in both. Indeed, recent studies support the presence of a reductive step in Fe 0 uptake by Fe-limited cyanobacteria (Salmon et al, 2006;Lis and Shaked, 2009;Kranzler et al, 2011;Kranzler et al, 2014). This is consistent with the idea that the upper limit to iron uptake is fixed by the same maximum in the rate of Fe(III) reduction per S.A. as in eukaryotic phytoplankton.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The surprising similarity of S.A. normalized Fe 0 uptake between cyanobacteria and eukaryotic phytoplankton ( Figure 5) implies that similar factors may be responsible for the upper limit on Fe uptake in both. Indeed, recent studies support the presence of a reductive step in Fe 0 uptake by Fe-limited cyanobacteria (Salmon et al, 2006;Lis and Shaked, 2009;Kranzler et al, 2011;Kranzler et al, 2014). This is consistent with the idea that the upper limit to iron uptake is fixed by the same maximum in the rate of Fe(III) reduction per S.A. as in eukaryotic phytoplankton.…”
Section: Discussionsupporting
confidence: 77%
“…Reductive Fe uptake involves an integral reductive step before internalization of Fe via the cell plasma membrane. This prevalent pathway has been demonstrated in the uptake of Fe 0 and organically bound Fe compounds in fresh water and marine prokaryotic and eukaryotic phytoplankton (Allnutt and Bonner, 1987;Jones et al, 1987;Eckhardt and Buckhout, 1998;Maldonado and Price, 2001;Lis and Shaked, 2009;Kranzler et al, 2011). Siderophoremediated Fe uptake involves direct transport of the ferric-siderophore complex into the cell where Fe is released from the chelating ligand.…”
Section: Introductionmentioning
confidence: 95%
“…Calculations suggest that this pool should support partial growth of cyanobacteria in even the most iron-depleted oceanic regions 14 . Furthermore, one of the organisms in the HRG set, Synechococcus WH8102, may be able to reduce Fe(III)-siderophore complexes, thereby increasing the pool of unchelated iron for uptake 15 , although the molecular identity of the reductase is unknown.…”
Section: Genomic and Functional Characterizationmentioning
confidence: 99%
“…Among cyanobacteria, the analysis of both laboratory cultures and natural populations suggested the existence of a reductive iron uptake pathway (Rose and Waite, 2005;Lis and Shaked, 2009). In a previous work we demonstrated that the unicellular cyanobacterium, Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%